Α-DTC70 fullerene performs significantly better than β-DTC70 as electron transporting material in perovskite solar cells. Issue 20 (22nd April 2020) - Castro, Edison; Fernandez-Delgado, Olivia; Artigas, Albert; Zavala, Gerardo; Liu, Fang; Moreno-Vicente, Antonio; Rodríguez-Fortea, Antonio; Velasquez, José D.; Poblet, Josep M.; Echegoyen, Luis
Abstract : In this work, two new C70 isomers α and β bis(2-(thiophen-2-yl)ethyl)-C70 -fullerene mono-adducts (DTC70 ) were synthesized, characterized and used as electron transporting materials (ETMs) in perovskite solar cells (PSCs). Abstract : In this work, two new C70 isomers, α and β bis(2-(thiophen-2-yl)ethyl)-C70 -fullerene mono-adducts (DTC70 ), were synthesized, characterized and used as electron transporting materials (ETMs) in perovskite solar cells (PSCs). Our results show that the α isomer improves both the J sc and FF values of the devices, when compared to the results for the β-isomer and to those for phenyl-C70 -butyric acid methyl ester (PC71 BM ), used as control. Devices based on α-DTC70 achieved a power conversion efficiency (PCE) of 15.9%, which is higher than that observed with PC71 BM (15.1%).